Endoprosthetic growth module mechanism for the skeletally immature - Parsons, Adam Thane (Department of Mechanical Engineering, 2015)
Limb salvage surgery for the treatment of osteosarcoma in the skeletally immature necessitates the development of an endoprosthetic replacement, capable of extending at a rate comparable to that of natural growth without surgical intervention. Currently available devices require only physician facilitated extensions but often result in undesirable infrequent large extensions. They also commonly contain ferromagnetic materials which eliminate MRI imaging as a means of follow-up assessment. Thus, there is a need to develop a non-ferromagnetic device capable of carrying out frequent minor extensions comparable to natural growth. This dissertation details the design of an extendible endoprosthesis overcoming some of these issues. The scope is limited to the design and development of such a device and its control.